Does Islamic Financial Development Reduce Carbon Emissions? Evidence from OIC Countries - Nadya Setiawati; Daryn Salsabila (University of Darussalam Gontor, 2022)
Islamic finance has great potential in encouraging the development of social and economic infrastructure. The rapid improvement of the Islamic finance sector and the increasingly good economic growth have a positive impact on infrastructure development in the Countries of the Organization Islamic Cooperation (OIC). The study analyzed the impact of the development of the Islamic financial sector on CO2 emissions in 12 OIC countries including the United Arab Emirates, Indonesia, Jordan, Kazakhstan, Kuwait, Lebanon, Malaysia, Nigeria, Pakistan, Saudi Arabia, Sudan and Turkey from 2013 to 2018. The dependent variables used are CO2 emissions, while independent variables include GDP per capita, Sukuk issuance, total sharia-compliant, total energy consumption, and industry value-added. The study used the Panel Corrected Standard Error (PCSE) method and robustness using the Newey-West standard error model. Results from the study showed that GDP per capita and industry value added significantly increased CO2 emissions. Conversely, Islamic financial development variables namely Sukuk issuance and total sharia-compliant have a negative and significant impact on CO2 emissions. This research suggests for policymakers to further encourage sustainable development of Islamic finance to encourage energy efficiency and renewable energy production and consumption to reduce CO2 emissions and maintain environmental quality.